Application of The Think Talk Write (TTW) Method Oriented Towards Self-Efficacy of Students To Improve Indonesian Language Learning Outcomes - Fatimah, Garnis; Cahyani, Isah; Juhana, Juhana (Publikasi Indonesia, 2023)
This research aims to found out: (1) the students’ Indonesian grade use Think Talk Write (TTW) better compared than the students’ Indonesian grade use Cooperative Learning method, (2) the students’ Indonesian grade by high self efficacy development compared with moderate self efficacy development, the students’ Indonesian grade by high self efficacy development compared with low self efficacy development, and the students’ Indonesian grade by moderate self efficacy development compared with low self efficacy development, (3) is there an interaction between Think Talk Write (TTW) method and Conventional learning method about the students’ self efficacy development on the increase of Indonesian’s grade . The type of this research is quasi experimental with design factorial of 2 x 3. The population in this research were all students in the third grade of SD Negeri Mekarasih of Cihampelas Subdistrict of Bandung Barat Regency selected by chosen without random assignment into III B as the experiment class and III A as control class. The data of questionnaires result and tests of Indonesian are analyzed by using the test of analyze two way anova with Microsoft Excel 2016. Base on the founded data analyze, the research points are identified as follows: First, the test result of datas mean there are differences between Think Talk Write (TTW) method and Cooperative Learning method about the Indonesian’s grade, then the decision is learning Indonesian using Think Talk Write (TTW) method gives better influence than learning Indonesian using Conventional learning method. Second, the test result of datas give explanation that there are differences comprehention between students’ self efficacy categories development and Indonesian’s grade. This is because the tests result show that there are the differences Indonesian learning ability between students’ high self efficacy, students’ moderate self efficacy, and students’ low self efficacy. The students’ high self efficacy development has understanding ability of Indonesian better than students’ moderate self efficacy developments. Third, the test result of datas give explanation that there is no interaction between Cooperative Learning method and students’ self efficacy categories development about the Indonesian’s grade.